Modern approaches to treatment of acute anaerobic paraproctitis - M. A. Yegorkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2011)
The aim of review. Analysis of up-to-date approaches to treatment of acute anaerobic paraproctitis (AP).Original positions. The majority of researchers agree that anaerobic directivity of inflammatory process at AP is determined by high load and virulence of the infectious agent on a background of decrease of immune resistance of the body. Unsatisfactory results of treatment are related to the delayed encounter of the majority of patients (81,8%) for specialized aid, and also to late diagnostics. High mortality and morbidity at anaerobic paraproctitis are caused by rapid generalization of process, development of septic states and multiorgan failure.Conclusion. Ways of improvement of treatment results at AP – perfection of tactical and technological level of surgical interventions, improvement of preoperative preparation, methods of anaestesia, prevention of acute cardiopulmonary failure. In postoperative period antibiotic therapy by carbapenems or last generation penicillins in maximally allowed doses, treatment of organ dysfunction, control of regenerative processes in the vast wounds formed after radical operations is recommended.